2020
DOI: 10.1371/journal.pbio.3001001
|View full text |Cite
|
Sign up to set email alerts
|

Biparental contributions of the H2A.B histone variant control embryonic development in mice

Abstract: Histone variants expand chromatin functions in eukaryote genomes. H2A.B genes are testis-expressed short histone H2A variants that arose in placental mammals. Their biological functions remain largely unknown. To investigate their function, we generated a knockout (KO) model that disrupts all 3 H2A.B genes in mice. We show that H2A.B KO males have globally altered chromatin structure in postmeiotic germ cells. Yet, they do not show impaired spermatogenesis or testis function. Instead, we find that H2A.B plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 92 publications
2
11
0
Order By: Relevance
“…To begin to explore their function, we examined their expression in mammals. Similar analyses had previously revealed putative germline-specific functions of many rapidly evolving H2A variants ( Molaro et al 2018 , 2020 ). Prior studies have shown that some H2B variants are primarily expressed in testes of rodents, bull, or human.…”
Section: Resultssupporting
confidence: 81%
“…To begin to explore their function, we examined their expression in mammals. Similar analyses had previously revealed putative germline-specific functions of many rapidly evolving H2A variants ( Molaro et al 2018 , 2020 ). Prior studies have shown that some H2B variants are primarily expressed in testes of rodents, bull, or human.…”
Section: Resultssupporting
confidence: 81%
“…To begin to explore their function, we examined their expression in mammals. Similar analyses had previously revealed putative germline-specific functions of many rapidly evolving H2A variants (Molaro, et al 2018; Molaro, et al 2020). Prior studies have shown that some H2B variants are primarily expressed in testes of rodents, bull, or human.…”
Section: Resultssupporting
confidence: 80%
“…Although several H2B variants appear to be highly enriched in the male germline, this does not eliminate the possibility that they might play important roles during oogenesis and early embryogenesis. For example, the H2A.B variant is testis-enriched in expression but nevertheless plays key roles in oogenesis and post-implantation development in mice (Molaro, et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The ‘out-of-testis’ hypothesis predicts that the male germline provides an initial ‘gene nursery’ for evolutionary innovation, with diversification subsequently broadening its expression profile ( Assis and Bachtrog, 2013 ; Vinckenbosch et al, 2006 ; Nyberg and Carthew, 2017 ). Recent studies of histone variants, which were originally thought to be ‘testis-specific’ in Drosophila and mammals, based on RT-PCR data, demonstrated that their expression and function also extends to females ( Kursel et al, 2021 ; Molaro, 2020 ). Similarly, Umbrea, which is highly testis-enriched, is required for chromosome segregation more broadly ( Ross et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%